Recent Advances in Coke Management for Dry Reforming of Methane over Ni-Based Catalysts - Xu, Zhenchao; Park, Eun Duck (Catalysts, 2024)
The dry reforming of methane (DRM) is a promising method for controlling greenhouse gas emissions by converting CO2 and CH4 into syngas, a mixture of CO and H2. Ni-based catalysts have been intensively investigated for their use in the DRM. However, they are limited by the formation of carbonaceous materials on their surfaces. In this review, we explore carbon-induced catalyst deactivation mechanisms and summarize the recent research progress in controlling and mitigating carbon deposition by developing coke-resistant Ni-based catalysts. This review emphasizes the significance of support, alloy, and catalyst structural strategies, and the importance of comprehending the interactions between catalyst components to achieve improved catalytic performance and stability.
Keywords: carbon dioxide; coke resistance; dry reforming; methane; nickel; syngas